Determinants of length for age Z scores among children aged 6–23 months in Central Java, Indonesia: a path analysis - Kartasurya, Martha Irene; Syauqy, Ahmad; Suyatno, Suyatno; Dewantiningrum, Julian; Nuryanto, Nuryanto; Sunarto, Sunarto; Isnawati, Muflihah; Nurcahyani, Yusi Dwi; Wati, Erna Kusuma; Hapsari, Pramesthi Widya; Samsudin, Mohamad; Fuada, Noviati (Frontiers in Nutrition, 2023)
Introduction Length for Age Z (LAZ) score determinants are complex and vary among different areas, but it is important for designing effective and efficient strategies to decrease stunting prevalence among children under 2 years. This study aimed to investigate the determinants of LAZ scores among children under 2 years in Central Java, Indonesia. Methods This study was conducted on the 2021 Indonesian Nutritional Status Study (INSS) dataset, which was a cross-sectional survey. Data on 3,430 children aged 6–23 months from Central Java province were derived from the 2021 INSS data. After missing data elimination, 3,238 subjects were included in the analysis. Determinant factors included direct and indirect factors. Direct factors were the mother's age, birth weight Z score (BWZ), birth length Z score (BLZ), exclusively breastfed history, dietary diversity scores (DDS), empty calorie drink consumption, unhealthy snacks consumption, and infections. Indirect factors were early initiation of breastfeeding (EIBF) and posyandu (integrated health post) utilization. Underlying factors were socioeconomic status (SES) and the mother's education. Bivariate analyses and multiple linear regressions were conducted. A path analysis with a hypothesized model based on the UNICEF conceptual framework was also performed. Results Stunting, wasting and underweight proportions among the subjects were 19.1%, 7.6% and 12.3%, respectively. The mean LAZ scores were −0.95 ± 1.22; the mother's age was 29.7 ± 5.95 years; BWZ was −0.47 ± 0.97; BLZ was −0.55 ± 1.05; and DDS was 4.45 ± 1.51. The infection proportion among the subjects was 28%. BWZ and BLZ were positively correlated to LAZ scores, with r = 0.267 (p < 0.01) and r = 0.260 (p < 0.01), respectively. The mother's age was negatively correlated to LAZ scores with r = −0.041 (p < 0.05). Maternal education was positively correlated to SES but had no direct effect on LAZ scores. LAZ score determinants of BLZ (p < 0.001) and SES (p < 0.001) showed positive direct associations with LAZ scores, but the mother's age (p = 0.039), exclusively breastfed history (p < 0.001), and empty calorie drinks consumption (p < 0.001) had negative associations with LAZ scores. Conclusion To prevent stunting among children aged 6–23 months in Central Java, Indonesia, intervention programs to increase the nutritional status of women at child-bearing age and nutrition education on child feeding practices should be conducted more efficiently and effectively.